PELATIHAN KETRAMPILAN SOSIAL UNTUK MENGURANGI SIMTOM NEGATIF PADA PENDERITA SKIZOFRENIA - , YENY DURIANA WIJAYA, Drs. Subandi, MA, Ph.D, Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Schizophrenia is a mental illness that usually caused negative stigma, both self and public stigma. During rehabilitation process, people with schizophrenia tend to be dominated by negative symptoms. One of the efforts that can be done to improve social skills and reduce the negative symptoms is to give social skills training. The purpose of this study is to analyze the effectiveness of social skills training to reduce negative symptoms in people with schizophrenia. The participants were people with schizophrenia who were undergoing rehabilitation process in Panti Sosial Bina Karya, Yogyakarta (rehabilitation institution run by regional government of Yogyakarta). The study recruited 8 people with schizophrenia who is undergoing rehabilitation process. Negative symptoms assessed by Negative Symptoms Scale and Social Skills Scale. Non parametric Mann Whitney Test (U test) used to analyze the quantitative data. The qualitative data were obtained from observations and interviews. The results of quantitative analysis showed that there is a difference between the experimental and control groups for social skills variables Z = -2.312 with p = 0.021 (p <0.05) and negative symptoms variable value Z = -2.100 with p = 0.036 (p <0, 05). Result showed that social skills training effectively improve social skills and reduce negative symptoms in people with schizophrenia undergoing rehabilitation process.